A STUDY OF AUTO-REINFORCED MAGNETIC FLYWHEEL'S PERFORMANCE - MOHD KHAIRAN, SYAFIQ (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Advance development of technologies such as composite material and active magnetic bearings enable flywheel, a kinetic energy storage a more viable energy storage solution compared to static energy storage such as battery and capacitors. Numerous researches made to increase the potential of flywheel such as the aforementioned material development. However, these research aims at increasing the operational limits of the flywheel itself. This research centres around a novel design of a flywheel which known as the Auto-reinforced magnetic flywheel (AMFLY). Designed by Radikal Akbar, AMFLY alter the basic operational principle solely by addition of a reinforcing flywheel to the flywheel energy storage system to boost the performance. This is made possible by the application of mecha-magnetic features to the system. The concept will be proven through several analysis and experimental testing of the AMFLY prototype and simultaneously determines the optimal configuration of the system.